Drivers of customer satisfaction: perspectives from the food retail sector of an Arab nation. (2012) - Sohail, M. Sadiq; Anwar, Syed Aziz; Rabbie, Fuad Hossain
Customer satisfaction has come to occupy strategic heights given the growing competitiveness of the food retail market in Saudi Arabia. The purpose of this paper is to examine the key drivers of customer satisfaction. The paper examines the relationship among the extent of store familiarity, store atmosphere, price perception of products and availability of items based on cultural needs, and customer satisfaction. This study is based on a questionnaire survey. Based on a model developed for this study, the paper uses empirical research to determine these relationships. Findings of this study reveal that three of the four factors have influence on the satisfaction of customers in Saudi Arabia. Owing to limited sample size, however, the results of this study cannot be generalised for the entire Kingdom of Saudi Arabia. Nevertheless, this study makes a valuable contribution, given the fact that there is a dearth of empirical studies of this nature undertaken in the Middle East region.